Estudo da interferência do fator externo da posição do avaliador na avaliação subjetiva de superfície pavimentos asfálticos - Gasparini, Lucas Morelli [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Paving is responsible for providing users with trafficability, rolling comfort and safety, its performance tends to deteriorate after the start of rolling, making timely maintenance necessary. It is in this context that the Pavement Management System is established, a coordinated set of activities with the objective of optimizing resources and guaranteeing the quality of the road network. Two concepts are important for the PMS: usefulness, the pavement's ability to provide comfort and performance, and the temporal variation of serviceability. These parameters can be determined according to structural and functional aspects. Associated with thislatter is the Subjective Assessment, addressed in this work, whose objective is to establish the usefulness level of a given pavement through the Current Useful Value, following criteria related to rolling comfort. Due to its subjective aspect, the assessment is subject to interference from factors that are not directly linked to the quality of the pavement, such as the position of the evaluators in the vehicle and the speed of travel. The first being the object of this work, whose results indicate that the feeling of comfort inside a vehicle varies according to the position occupied, and tends to fluctuate more intensely the worse the condition of the pavement is.

A pavimentação é responsável por proporcionar aos usuários trafegabilidade, conforto ao rolamento e segurança, mas o seu desempenho tende a deteriorar após o início da rolagem, fazendo-se necessária a manutenção oportuna. É nesse contexto que se estabelece Sistema de Gerência de Pavimentos, um conjunto coordenado de atividades com o objetivo de otimizar recursos e garantir a qualidade da malha rodoviária. Dois conceitos são importantes para o SGP: serventia, a capacidade do pavimento em proporcionar conforto e desempenho, a variação temporal da serventia. Estes parâmetros podem ser determinados de acordo com aspectos estruturais e funcionais. Associado a este último, está a Avaliação Subjetiva, abordada neste trabalho, cujo objetivo é estabelecer o nível de serventia de determinado pavimento com base no Valor de Serventia Atual, seguindo critérios relacionados ao conforto ao rolamento. Devido ao seu aspecto subjetivo, a avaliação está sujeita a interferência de fatores que não estão diretamente ligados à qualidade do pavimento, como a posição dos avaliadores no veículo e a velocidade de percurso. Sendo o primeiro o objeto deste trabalho, cujos resultados obtidos indicam que a sensação de conforto dentro de um veículo varia de acordo com a posição ocupada, e tende a oscilar mais intensamente quão pior é a condição do pavimento.
Study of the interference of the external factor of the evaluator's position in the subjective assessment of asphalt pavements surface
Keywords: Pavement management system; Subjective evaluation of pavements; Current service value; Sistema de gerência de pavimentos; Avaliação subjetiva de pavimentos; Valor de serventia atual